Hubungan Komunikasi Terapeutik Perawat Dengan Tingkat Kecemasan Anak Usia Pra Sekolah (3-5 Tahun) Selama Hospitalisasi Di Ruang Rawat Inap Rumah Sakit Bhayangkara Kota Bengkulu Tahun 2025 - Amelia Putri; Delta Aprianti; Kartika Murya Ningrum (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Hospitalization is an experience that can cause anxiety in children, especially preschoolers (3–5 years old). The unfamiliar hospital environment, medical procedures, and the child's limited ability to understand the situation often cause children to show anxious responses such as crying, fear, and uncooperativeness. The problem in this study is that preschool-aged children are still found to experience anxiety during hospitalization, so effective nursing efforts are needed to overcome this. This study used a quantitative design with a cross-sectional approach. The population in this study were all preschool-aged children undergoing treatment at Bhayangkara Hospital, Bengkulu City. The sample consisted of 55 respondents selected using an accidental sampling technique. The research instrument used was a nurse therapeutic communication questionnaire to measure the level of anxiety in children. Data analysis was carried out univariately and bivariately using the Chi-Square test with a significance level of α = 0.05. The results showed that most nurses implemented therapeutic communication in the good category (45.5%) and most children experienced a level of no anxiety (43.6%). The results of the Chi Square test with a value of 0.000 (≤0.05) statistics indicate a significant relationship between nurses' therapeutic communication and the level of anxiety of preschool-aged children during hospitalization in the inpatient room of Bhayangkara Hospital, Bengkulu City in 2025. The conclusion of this study is that nurses' therapeutic communication plays an important role in reducing the level of anxiety of preschool-aged children during hospitalization. It is recommended that nurses continue to improve the quality of therapeutic communication as part of child nursing care, and that hospitals make therapeutic communication a standard in child nursing services.